2015
DOI: 10.1124/dmd.114.062604
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Enterocyte-Like Cells with Pharmacokinetic Functions from Human Induced Pluripotent Stem Cells Using Small-Molecule Compounds

Abstract: The small intestine plays an important role in all aspects of pharmacokinetics, but there is no system for the comprehensive evaluation of small-intestinal pharmacokinetics, including drug metabolism and absorption. In this study, we aimed to construct an intestinal pharmacokinetics evaluation system and to generate pharmacokinetically functional enterocytes from human induced pluripotent stem cells. Using activin A and fibroblast growth factor 2, we differentiated these stem cells into intestinal stem cell-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…We previously reported that human iPS cell-derived enterocyte-like cells had metabolic functions, such as drug-metabolizing enzyme activities and CYP3A4 inducibility (Iwao et al, 2015). Moreover, in this study, we demonstrated the drug transport characteristics in the enterocyte-like cells.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…We previously reported that human iPS cell-derived enterocyte-like cells had metabolic functions, such as drug-metabolizing enzyme activities and CYP3A4 inducibility (Iwao et al, 2015). Moreover, in this study, we demonstrated the drug transport characteristics in the enterocyte-like cells.…”
Section: Discussionmentioning
confidence: 48%
“…Moreover, it was indicated that the F a of drugs in humans can be estimated from permeability data of the enterocyte-like cell membrane. In our previous study, we found that the differentiated cells performed drug-metabolizing enzyme activities and CYP3A4 inducibility (Iwao et al, 2015). Taken together, the enterocyte-like cells may be useful as an appropriate model to comprehensively predict drug transport and metabolism in the intestine.…”
Section: Intestinal Transport In Human Ips Cell-derived Enterocytes 1665mentioning
confidence: 99%
See 2 more Smart Citations
“…The hiPSCs can serve as an attractive tool for drug development and studies of disease mechanisms 14 . Recently, differentiation procedures into IECs from hESCs or hiPSCs have been reported [8][9][10]15 . Human iPSCs possess high proliferative activity and can be differentiated into preferred cell types.…”
Section: Discussionmentioning
confidence: 99%